Diagnostic imaging. Oral and Maxillofacial - Koenig, Lisa J; Tamimi, Dania Faisal; Petrikowski, C. Grace; Perschbacher, Susanne E; Ruprecht, Axel; Hatcher, David; Potter, Brad J; Benson, Byron W; Harnsberger, H. Ric (Elsevier, 2017)
Bridging the gap between dentistry and medical radiology, this up-to-date volume covers the anatomic zones, imaging modalities, patient conditions, and presenting clinical signs and symptoms shared by dentistry and medicine. Written by oral and maxillofacial radiologists specifically for those using CT or CBCT technology, this unique title not only offers a dentist's perspective on oral and maxillofacial imaging but also benefits radiologists in the Head and neck field. Dr. Lisa Koenig and her expert author team provide carefully updated information in a concise, bulleted format, keeping you current with recent advances in oral maxillofacial radiology. (Back cover of book).
Keywords: ústa; zobrazování trojrozměrné; Imaging, Three-Dimensional; stomatologické nemoci; diagnostické zobrazování; Diagnosis, Differential; Mouth; zubní lékařství; Stomatognathic Diseases; maxila; Maxilla; diferenciální diagnóza; Diagnostic Imaging